2015
DOI: 10.1073/pnas.1420347112
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution toward an improved growth rate and a reduced resistance range inProchlorococcusstrains resistant to phage

Abstract: Prochlorococcus is an abundant marine cyanobacterium that grows rapidly in the environment and contributes significantly to global primary production. This cyanobacterium coexists with many cyanophages in the oceans, likely aided by resistance to numerous co-occurring phages. Spontaneous resistance occurs frequently in Prochlorococcus and is often accompanied by a pleiotropic fitness cost manifested as either a reduced growth rate or enhanced infection by other phages. Here, we assessed the fate of a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 84 publications
(113 reference statements)
3
55
0
Order By: Relevance
“…Thus, expression of island genes during infection may have led to their utilization by phages over evolutionary time and their stable incorporation into phage genomes . Third, phages serve as an important selective pressure influencing diversity and content of cell-surface genes in genomic islands (Avrani et al, 2011;Avrani and Lindell, 2015), the products of which are utilized by phage for attachment and entry into the host. Combined, these findings highlight the central role of hypervariable genomic islands in cyanobacterial host-phage interactions, serving as a central axis for host response and defense against phage infection, as well as a hotspot for dynamic gene exchange that continually reshapes the genomes of both host and phage.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, expression of island genes during infection may have led to their utilization by phages over evolutionary time and their stable incorporation into phage genomes . Third, phages serve as an important selective pressure influencing diversity and content of cell-surface genes in genomic islands (Avrani et al, 2011;Avrani and Lindell, 2015), the products of which are utilized by phage for attachment and entry into the host. Combined, these findings highlight the central role of hypervariable genomic islands in cyanobacterial host-phage interactions, serving as a central axis for host response and defense against phage infection, as well as a hotspot for dynamic gene exchange that continually reshapes the genomes of both host and phage.…”
Section: Discussionmentioning
confidence: 99%
“…These heterotrophs included strains isolated as contaminants of the Prochlorococcus cultures, such as the gammaproteobacterium Alteromonas sp. Subsequent reports from other research groups have confirmed that Prochlorococcus can be helped during growth in liquid (Sher et al, 2011) and semisolid (Avrani and Lindell, 2015) culture media by heterotrophic bacteria. Additionally, dilute lawns of Prochlorococcus are unable to grow on plates, unless rescued by patches of helper cells (Morris et al, 2008, and Fig.…”
Section: Introductionmentioning
confidence: 87%
“…When Avrani and colleagues [29] observed a similar response in viral resistant Prochlorococcus strains, they also found that the reduced growth rates increased after 7 months and that these strains reduced their resistance against the viruses [84]. The changes in growth rate and resistance occurred as independent events, indicating that the selection pressure on these phenotypes was decoupled.…”
Section: Discussionmentioning
confidence: 97%
“…As also tried in the current study, COR is often measured as reduction of growth rates in the resistant host [23,24,25,26,27], but other CORs, like altered susceptibility to other viruses and possibly also to some bacteria [85], have also been argued [29,84,86,87,88]. Trade-off might also emerge when strains with different resistance capacities are put under competition for a limited level of nutrients [30,33,89,90], and this is the logical follow up to our study.…”
Section: Discussionmentioning
confidence: 99%